2015
DOI: 10.1371/journal.pone.0136841
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation for Childhood Asthma: A Systematic Review and Meta-Analysis

Abstract: ImportanceThere is growing evidence that vitamin D plays a role in the pathogenesis of asthma but it is unclear whether supplementation during childhood may improve asthma outcomes.ObjectivesThe objective of this systematic review and meta-analysis was to evaluate the efficacy and safety of vitamin D supplementation as a treatment or adjunct treatment for asthma.Data SourcesWe searched MEDLINE, Embase, CENTRAL, and CINAHL through July 2014.Study SelectionWe included RCTs that evaluated vitamin D supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 52 publications
(131 reference statements)
2
77
0
3
Order By: Relevance
“…Our results are in accordance with two recent meta-analyses of RCTs [15,16], which conclude that evidence is lacking to support regular use of vitamin D supplements for prevention of asthma exacerbations, but are in contrast with the findings of a recent Cochrane meta-analysis of RCTs [14]. Our findings for atopic dermatitis and IgE agree with recent observational studies and RCTs [3,4,9].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in accordance with two recent meta-analyses of RCTs [15,16], which conclude that evidence is lacking to support regular use of vitamin D supplements for prevention of asthma exacerbations, but are in contrast with the findings of a recent Cochrane meta-analysis of RCTs [14]. Our findings for atopic dermatitis and IgE agree with recent observational studies and RCTs [3,4,9].…”
Section: Discussionsupporting
confidence: 91%
“…A Cochrane review of placebo-controlled trials, including 435 children and 658 adults, concluded that vitamin D is likely to reduce the risk of severe asthma exacerbation and healthcare use due to asthma, though children and those with severe asthma were underrepresented in the included studies [111**]. These findings are in accordance with other systematic reviews [112,113]. …”
Section: Vitamin D Supplementationsupporting
confidence: 73%
“…Recent meta‐analyses suggest that vitamin D supplementation may reduce the likelihood of asthma exacerbation (Riverin et al. ; Martineau et al. ), and it will be important to determine whether treatment is more effective in individuals that are vitamin D deficient prior to commencing vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%